Analysis of Sustainable Fisheries Practices and Their Impact on Marine Ecosystem Conservation - Ahmad Fauzan; Laili Khotimah (Journal of Marine Fisheries, 2025)
Sustainable fisheries practices have become a central issue in marine resource management due to increasing pressure on marine ecosystems caused by overfishing, habitat degradation, and climate change. Unsustainable fishing activities have led to declining fish stocks and ecosystem imbalance, threatening both environmental sustainability and coastal livelihoods. This study aims to analyze the role of sustainable fisheries practices in supporting marine ecosystem conservation and to identify key factors influencing their effectiveness. The research employs a qualitative systematic literature review approach by examining peer-reviewed international and national journal articles published between 2012 and 2025. Data were analyzed through thematic content analysis focusing on ecological, institutional, and socio-economic dimensions of sustainable fisheries. The results indicate that ecosystem-based fisheries management, conservation areas, regulatory compliance, and community participation significantly contribute to maintaining marine biodiversity and ecosystem resilience. However, implementation challenges remain, particularly in governance effectiveness, enforcement capacity, and economic trade-offs. The study concludes that sustainable fisheries practices can effectively support marine ecosystem conservation when integrated with adaptive governance frameworks and stakeholder collaboration. These findings provide theoretical contributions to sustainable marine resource management and practical implications for policymakers in strengthening fisheries governance systems.